Penerapan Pembelajaran Deep Learning pada Pendidikan Kesetaraan Paket C di SPNF SKB Kota Semarang - Kanzabella Dewi Savera; Mintarsih Arbarini (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to describe the implementation of Deep Learning that integrates the dimensions of mindful, meaningful, and joyful learning in Package C equivalent education at SPNF SKB Semarang City. The research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation studies. The research subjects included tutors, learners, and the head of the institution. The results show that the implementation of the three deep learning stages was effective. Mindful learning was reflected in the learners' awareness of learning objectives and reflection practices facilitated by tutors. Meaningful learning was achieved by linking the material to the learners' life experiences, making learning more contextual and meaningful. Meanwhile, joyful learning was created through a comfortable classroom atmosphere, varied activities, and the active involvement and enthusiasm of the learners. Overall, this approach had a positive impact on increasing learning awareness, meaningfulness, engagement, and an enjoyable learning experience for adult learners. This study concludes that the deep learning framework is relevant and transformative for improving the quality of contextual learning in equivalent education, and provides practical implications such as the need for tutor training, development of contextual teaching materials, and a sustainable support system.